Tinjaun Yuridis Terhadap Permohonan Dispensasi Nikah Anak Dibawah Umur: (Studi Penetapan Pengadilan Agama Kraksaan Perkara Nomor 0092/PDT.P/2021/PA-KRS) - HA. Djazim Ma'shum; Pangestu Meyta TW (JUSTNESS - Jurnal Hukun dan Agama, 2021)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the one and only God based on law number 1 of 1974 concerning marriage. This research is a literature study with the title "Juridical Review of Applications for Dispensation for Marriage for minors (study of the determination of the Kraksaan Religious Court) Number 0092/pdt.p/2021/pa-krs", the problems examined in this study and the objectives are first to find out , examines and analyzes what is behind the submission of a marriage dispensation application, secondly to examine and analyze how the judge's considerations in determining the application for a marriage dispensation in case number 0092/pdt.p/2021/pa-krs. In this research, using a normative juridical approach, which describes and explains what factors are behind the submission of a marriage dispensation application and then associated with the judge's considerations in determining marriage dispensation cases, so as to produce a concrete and clear understanding. From the results of this study, it can be concluded that, firstly, in general, the factors behind the filing of a marriage dispensation application are influenced by several economic factors, social limitations factors, secondly that the consideration of the Panel of Judges in determining the application for a marriage dispensation is case number 0092/pdt.p/2021/pa- krs cannot be accepted. Keyword: Marriage Dispensation, Minors